EXPERIENCES OF ACADEMICIANS DURING COVID-19 DURING ONLINE LEARNING IN UNIVERSITI MALAYSIA SARAWAK - KALVINAH, CHANDRAN (Universiti Malaysia Sarawak (UNIMAS), 2021)
Since the Covid-19 pandemic has spread throughout the whole world, the Government itself decided to do a subsequent lockdown in many countries. So, the tertiary education institutions have decided to have online classes and sessions. This transition has not only been stressful to students, but the one who is conducting the classes, the academicians and lecturers are facing so much of struggles. It is not easy as physical classes where they can teach their students. Online classes itself has so much of challenges. The pandemic has been much so worse, so they have to stick to online classes. This goes beyond digitalization in the narrow senses and also facing issues and challenges such as students financing and network issues. The objective of this study is to learn the experiences of academicians during Covid-19 in Universiti Malaysia Sarawak. This study was carried out in a government university, by interviewing five (5) lecturers as informants. The data analysis procedure which was used in this study is thematic analysis.